cROSsing the Line: Between Beneficial and Harmful Effects of Reactive Oxygen Species in B-Cell Malignancies - Domka, Krzysztof; Goral, Agnieszka; Firczuk, Malgorzata (Frontiers in Immunology, 2020)
B-cell malignancies are a heterogeneous group of hematological neoplasms derived from cells at different stages of B-cell development. Recent studies revealed that dysregulated redox metabolism is one of the factors contributing to the pathogenesis and progression of B-cell malignancies. Elevated levels of oxidative stress markers usually correlate with the advanced stage of various B-cell malignancies. In the complex tumor microenvironment, reactive oxygen species affect not only malignant cells but also bystander cells, including immune cells. Importantly, malignant cells, due to genetic dysregulation, are able to adapt to the increased demands for energy and reducing equivalents via metabolic reprogramming and upregulation of antioxidants. The immune cells, however, are more sensitive to oxidative imbalance. This may cause their dysfunction, leading to immune evasion and tumor progression. On the other hand, the already imbalanced redox homeostasis renders malignant B-cells particularly sensitive to further elevation of reactive oxygen species. Indeed, targeting antioxidant systems has already presented anti-leukemic efficacy in preclinical models. Moreover, the prooxidant treatment that triggers immunogenic cell death has been utilized to generate autologous anti-leukemic vaccines. In this article, we review novel research on the dual role of the reactive oxygen species in B-cell malignancies. We highlight the mechanisms of maintaining redox homeostasis by malignant B-cells along with the antioxidant shield provided by the microenvironment. We summarize current findings regarding therapeutic targeting of redox metabolism in B-cell malignancies. We also discuss how the oxidative stress affects antitumor immune response and how excessive reactive oxygens species influence anticancer prooxidant treatments and immunotherapies.